Foreign Takeovers: No Negative Effects on Employment and Productivity - Anselm Mattes (Weekly Report, 2010)
When foreign companies acquire German firms as part of an acquisition or merger, government representatives and unions often fear production relocation as well as a loss of influence and rising unemployment. The discussion concerning the planned acquisition of the Hochtief Group by a Spanish corporation provides a powerful example of these concerns. Approximately three percent of German firms are in foreign ownership. These companies employ nearly seven percent of all employees in Germany. They are not only larger but also more productive and export orientated than the average domestic firms. Some of these represent newly established firms, but in many cases existing companies were acquired by foreign companies. Preferred targets of foreign takeovers are both highly productive firms as well as relatively unproductive companies. Domestic enterprises with an average productivity level are less frequently targeted. An analysis of the effects of foreign acquisitions indicates that - at least in the short run - no significant effects on employment or productivity can be observed. Consequently neither claims of globalization critics that foreign investors act as "locusts" nor hopes of considerable boosts in productivity are justified. Hence, existing formal and informal restrictions of foreign takeovers are dispensable and even potentially damaging.
Keywords: F23; J23; 330; M&A; Inward FDI; Foreign takeover; Employment; Productivity